2019
DOI: 10.13189/ujer.2019.071115
|View full text |Cite
|
Sign up to set email alerts
|

Accounting as a Choice of Academic Programme: A Comparative Study between Malaysian and Indonesian First-year Under-graduate Accounting Students

Abstract: Although rapid and tremendous economy development worldwide has sparked a massive demand for accountants, developing nations like Malaysia and Indonesia are dearth of this profession. Triggered by this mismatch and emulating variables postulated by Theory of Reasoned Action, the objectives of this study are to decipher intention to choose accounting as academic programme with regards to attitude towards accounting profession and social group influence in Malaysian and Indonesian contexts. A total of 350 Malays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…These discoveries provide useful insights for policy makers, accounting professional bodies and higher education to formulate policies exposing students and social groups on the importance of incentives and prospects of the accounting profession. It is hoped that the initiatives will produce many accountants and thus expedites the countries' aspiration of becoming full-developed nations in due time [6].…”
Section: Resultsmentioning
confidence: 99%
“…These discoveries provide useful insights for policy makers, accounting professional bodies and higher education to formulate policies exposing students and social groups on the importance of incentives and prospects of the accounting profession. It is hoped that the initiatives will produce many accountants and thus expedites the countries' aspiration of becoming full-developed nations in due time [6].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, normative views impact one's decision to pursue a certain job route based on the experiences and perspectives of others [39], which is "a belief about whether every referral agree or dissagre about the behaviour" [52]. It can be concluded that when students are deciding whether to pursue a career in accounting, behavioural and normative belief are important since they determine the intention to conduct activities [79].…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…For the specific in Indonesia, whereby the number of certified public accountant over the total population ratio is merely 0.0004%. The country has only 487 public accounting firms with 1,008 Certified Public Accountant (CPA) as registered partners over population of 230 million [81]. As expressed by the president of the Indonesian Institute of Certified Public Accountants (IAPI), Tarkosunaryo.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural belief is a behaviour that is considered to be intuitive and will lead to certain results; in an outcome evaluation, one treats the possibility of evaluating the accounting industry to achieve a good prospect. Behavioural beliefs and outcome evaluation are two functions that affect behavioural attitudes (Zakaria et al, 2019).…”
Section: 2)mentioning
confidence: 99%
“…A combination of normative beliefs and motivation to comply with subjective norms. Normative beliefs refer to a person's beliefs, group pressure given by social groups and others, and have an impact on the decision to choose to account as an academic major; in compliance motivation, refers to how a person is motivated to comply with the expectations of social groups condition (Zakaria et al, 2019).…”
Section: 2)mentioning
confidence: 99%